2003
DOI: 10.1080/mmy.41.2.83.87
|View full text |Cite
|
Sign up to set email alerts
|

Thymus invasion and atrophy induced byParacoccidioides brasiliensisin BALB/c mice

Abstract: Literature has shown that immunosuppression observed in systemic mycosis can be related to damage in primary lymphoid organs. We have studied the immunopathological alterations induced experimentally by Paracoccidioides brasiliensis in these organs. In this work, thymic alterations induced in BALB/c mice during acute and chronic stages of infection are described. It was observed that P. brasiliensis is able to invade the thymic microenvironment, inducing severe atrophy characterized by degeneration of the cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
0
9
0
3
Order By: Relevance
“…We have previously shown that thymic atrophy, in an acute experimental infection model of PCM, is characterized by histological changes, with loss of cortical–medullary delimitation, and the intrathymic presence of parasites [ 18 ]. Thymic atrophy has been described as a common consequence of many infectious diseases and metabolic disturbances, such as malaria, Chagas disease, human immunodeficiency virus (HIV) infection, diabetes and malnutrition [ 19 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that thymic atrophy, in an acute experimental infection model of PCM, is characterized by histological changes, with loss of cortical–medullary delimitation, and the intrathymic presence of parasites [ 18 ]. Thymic atrophy has been described as a common consequence of many infectious diseases and metabolic disturbances, such as malaria, Chagas disease, human immunodeficiency virus (HIV) infection, diabetes and malnutrition [ 19 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Differentiation and maturation of T-cells occurs in the thymus, thus integrity of the thymic microenvironment is crucial for the maturation of thymocytes. Experimental data in a murine model of acute paracoccidioidomycosis shows that infection with Paracoccidioides yeast cells promotes thymus atrophy as a consequence of epithelial cell spatial disarrangement and increased gene expression of inflammatory mediators [168, 169]. These results suggest that a decreased differentiation of pathogen-specific T-cells leads to host immunosuppression, favoring Paracoccidioides spp.…”
Section: Disseminationmentioning
confidence: 99%
“…The thymus is a central T-lymphocyte organ of the immune system that generates functional naive T cells for cellular immunity and depletes self-reactive T cells for self-tolerance [ 7 , 8 ]. The thymus is very sensitive to insults, such as whole-body viral (influenza) [ 9 ], parasitic ( Trypanosoma cruzi ) [ 10 ], and fungal infections ( Paracoccidioides brasiliensis ) [ 11 ], which are common agents of infectious diseases [ 12 ]. Typically, the thymus shows acute atrophy after insult, resulting in modifications of thymic structure and alterations in naive T cell output to the periphery.…”
Section: Introductionmentioning
confidence: 99%